2010
DOI: 10.4314/bajopas.v1i1.57539
|View full text |Cite
|
Sign up to set email alerts
|

Current trend in antimicrobial susceptibility pattern of <i>Clostridium tetani</i> isolated from soil samples in Kano

Abstract: The need for a regular assessment of the antimicrobial sensitivity patterns among tetanus causing as well as infectious members of Clostridia found in soil-human settlement provides a justification for the present study. Accordingly, soil from various locations of Bayero University Campus, Kano was screened for the isolation of C. tetani by anaerobic culturing procedures. The organism was detected in 60% of the soil samples. The isolates were tested against commonly prescribed drugs including sparfloxacin, cip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
2
1
Order By: Relevance
“…However, 100% failed with 17-20 mm against C. tetani when isolated from soil. This does not agree with the data of Bukar et al [9], who reported a value of 26 mm for C. tetani.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, 100% failed with 17-20 mm against C. tetani when isolated from soil. This does not agree with the data of Bukar et al [9], who reported a value of 26 mm for C. tetani.…”
Section: Discussioncontrasting
confidence: 99%
“…At the international level, the present results are also comparable with the reports of Gashe et al [11] from Ethiopia and Wu et al [12] from China. The full activity of metronidazole-containing preparations against C. tetani in wild soil is also consistent with reports from a study by Bukar et al [9].…”
Section: Discussionsupporting
confidence: 91%
“…The collected samples were stored in sterile plastic tubes and frozen at −70 °C within 6 to 12 h for later analysis [16,17,18,19].…”
Section: Methodsmentioning
confidence: 99%
“…Previously, the isolation of the C. tetani from the different soil samples was carried out by Bukar and his colleagues using an anaerobic culturing technique. 25 In this study, the isolation of the clinical bacterial isolates of C. tetani was performed from clinically diagnosed tetanus patients. 26 As a site of infection was obvious in our patients, this increased the isolation rate of C. tetani by inoculating the primary media with C. tetani isolates.…”
Section: Discussionmentioning
confidence: 99%